Translation of task-evoked negative BOLD response into aging and Alzheimer's disease: a systematic review of the current literature - Bardiya Ghaderi Yazdi; Qolamreza R. Razlighi (Journal of Translational Medicine)
Abstract Background Aging, mild cognitive impairment (MCI), Alzheimer’s disease (AD), and individuals at risk for AD are associated with impaired negative blood-oxygen-level-dependent (BOLD) response (NBR) in task-evoked functional magnetic resonance imaging (fMRI) studies. In addition, autosomal dominant AD patients have exhibited NBR alterations in the default mode network (DMN) regions nearly a decade before any accumulation of amyloid-β (Aβ) or tau and subsequent memory decline. Studies examining exclusively the NBR are rare in clinical settings, but some existing studies using task-evoked fMRI also report alterations in the NBR. However, in many studies, NBR is often disregarded, left lingering in the shadows, or, more generally, masked out as a bothersome noise. Methods We reviewed the Embase, Scopus, and PubMed databases, and forward and backward citation tracking for studies published up to 6/11/2024. Included articles detailed the use of task-evoked fMRI (tb-fMRI) to investigate aging, AD, mild cognitive impairment (MCI), and early tau or Aβ deposition, with all results reported on NBR. Findings From 319 records identified for aging, 154 records for tau or Aβ, and 159 records for AD and MCI, 42, 14, and 9 papers were included, respectively. Forward and backward citation tracking added 44, 3, and 55 papers, respectively resulting in 167 studies with 11310 individuals. A significantly reduced magnitude of NBR in some regions of the DMN in healthy aging compared with young participants and individuals with elevated Aβ levels, MCI, and AD compared to healthy aging was found in 57, 12, 17, and 14 studies, respectively. Interpretation This review highlights the DMN NBR’s importance in the AD continuum and underscores its potential as an early diagnostic biomarker when pharmacological treatment options can still alter the disease course.